GC-MS Analysis of Insecticidal Essential Oil of Aerial Parts of Echinops latifolius Tausch - Xin Chao Liu; Xianghong Hao; Ligang Zhou; Zhi Long Liu (Journal of Chemistry)
The roots of Echinops latifolius Tausch (Asteraceae) have been used in the traditional medicine. However, no report on chemical composition and insecticidal activities of the essential oil of this plant exists. The aim of this research was to determine chemical composition and insecticidal activities of the essential oil of E. latifolius aerial parts against maize weevils (Sitophilus zeamais Motschulsky) for the first time. Essential oil of E. latifolius aerial parts at flowering stage was obtained by hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC-MS). A total of 35 components of the essential oil of E. latifolius aerial parts were identified. The major compounds in the essential oil were 1,8-cineole (19.63%), (Z)-β-ocimene (18.44%), and β-pinene (15.56%) followed by β-myrcene (4.75%) and carvone (4.39%). The essential oil of E. latifolius possessed contact toxicity against S. zeamais with an LD50 value of 36.40 µg/adult. The essential oil also exhibited fumigant toxicity against S. zeamais with an LC50 value of 9.98 mg/L. The study indicates that the essential oil of E. latifolius aerial parts has a potential for development into a natural insecticide/fumigant for control of insects in stored grains.